2022
DOI: 10.1002/wsb.1391
|View full text |Cite
|
Sign up to set email alerts
|

Adult white‐tailed deer survival in hunted populations on public and private lands

Abstract: Estimates of sex‐ and age‐specific survival are important for guiding population management decisions for white‐tailed deer (Odocoileus virginianus). However, differences in deer survival between public and private lands can exist and, if unaccounted for, may affect wildlife agencies' ability to effectively manage statewide and local deer populations. From 2014 to 2016, we radiocollared and monitored survival of 79 adult white‐tailed deer (141 deer‐years; 62 male, 79 female) on 2 public and 2 private propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
1
0
0
Order By: Relevance
“…Previous studies comparing survival of game species between public and private lands reported higher harvest and lower survival on public lands (Small et al 1991, Lebel et al 2012, Haus et al 2019). Conversely, our findings did not indicate differences in survival and harvest rates between public and private lands, which is comparable to recent work published on white‐tailed deer ( Odocoileus virginianus ) in Alabama (Wiskirchen et al 2023). Although hunting pressure could be greater on some public properties than on most private lands, it is plausible that increased pressure on public lands could be offset by lower per capita harvest success.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies comparing survival of game species between public and private lands reported higher harvest and lower survival on public lands (Small et al 1991, Lebel et al 2012, Haus et al 2019). Conversely, our findings did not indicate differences in survival and harvest rates between public and private lands, which is comparable to recent work published on white‐tailed deer ( Odocoileus virginianus ) in Alabama (Wiskirchen et al 2023). Although hunting pressure could be greater on some public properties than on most private lands, it is plausible that increased pressure on public lands could be offset by lower per capita harvest success.…”
Section: Discussionsupporting
confidence: 88%